Development of Safety Planning Using Risk Breakdown Structure to Improve Safety Performance on Construction Project: Development of Safety Planning Using Risk Breakdown Structure to Improve Safety Performance - Machfudiyanto, R.A.; Latief, Y.; Monang, A. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The bridge construction project, especially at the Elevated Trans Jakarta Road Project is a type of work with high complexity and is located in an open location, so many conditions of the potential hazards may arise. The lack of risks that can be identified and their control in safety planning documents will result in a continually arising job accident rate. The study objectives are to (i) identify the stages of the implementation, as well as the risk factors that have potential hazards, (ii), analyze the dominant risk factors in each stage of activity, and (iii) develop Safety Planning based on Regulation of Minister of Public Works No.05/PRT/M/2014 to improve the safety performance. The study was conducted qualitatively, by analyzing data on the perception of the questionnaire to the respondents who had experience in the project, and then the data were processed by Analytic Hierarchy Process (AHP) to get priority risk factors. The study results showed that there were 65 events of the risks which were identified as potentially dangerous, and 15 dominant risks that affected the OHS performance. Furthermore, the identification of risk response was performed, and risk level review was also conducted the risk response, review results showed a significant reduction in the risk level. It was concluded that OHS performance increased when safety planning was structured appropriately which was marked by decreased potential hazards following the applicable risk response.The bridge construction project, especially at the Elevated Trans Jakarta Road Project is a type of work with high complexity and is located in an open location, so many conditions of the potential hazards may arise. The lack of risks that can be identified and their control in safety planning documents will result in a continually arising job accident rate. The study objectives are to (i) identify the stages of the implementation, as well as therisk factors that have potential hazards, (ii), analyze the dominant risk factors in each stage of activity, and (iii) develop Safety Planning based on Regulation of Minister of Public Works No.05/PRT/M/2014 to improve the safety performance. The study was conducted qualitatively, by analyzing data on the perception of the questionnaire to the respondents who had experience in the project, and then the data were processed by Analytic Hierarchy Process (AHP) to get priority risk factors. The study results showed that there were 65 events of the risks which were identified as potentially dangerous, and 15 dominant risks that affected the OHS performance. Furthermore, the identification of risk response was performed, and risk level review was also conducted the risk response, review results showed a significant reduction in the risk level. It was concluded that OHS performance increased when safety planning was structured appropriately which was marked by decreased potential hazards following the applicable risk response.